Pengembangan Multimedia Pembelajaran pada Pembelajaran Informatika Kelas VIII di SMP Negeri 1 Kinali - Gusfianora, Fara; Eldarni, Eldarni; Syafril, Syafril; Rayendra, Rayendra (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to produce multimedia learning in informatics subjects using a 4D (four-D) development model which includes four stages, namely define, design, development, and dissemination. In the Development Step, a media validity test was carried out with two media expert validators and one material expert validator, then a practicality test was carried out on 30 junior high school grade VIII students to test the practicality of the multimedia learning developed. The results of the media validity assessment with validator I got a percentage of 94.67 with the category "very valid" and the results with validator II got a percentage of 97.33 with the category "very valid". The validity of the material obtained by the material validator obtained a percentage of 96.36 with the category of "very valid". Multimedia learning is said to be practical based on a practicality test with a percentage of 95.43 with the category "very practical". The steps taken in analyzing the respondents and then finding the percentage of the average results can be determined by the assessment criteria for the practicality test. Based on the results of the validity and practicality test, it can be concluded that the learning multimedia product in the informatics subject is very feasible to be used in the learning process.